Pacto Nacional pela Alfabetização na Idade Certa : possibilidades e percepções no contexto da formação docente - Leme, Josi Carolina da Silva (2015)
The actions of National Agreement for the Literacy at the Right Age, known as PNAIC, constitutes the most recent educational public policy proposal that intends to promote literacy for all children up to 8 years old. The proposal includes the teachers' training among these actions which brings a contribution to teachers' performance. As the national agreement settles in along with a qualitative research, this work aims to bring a case study to meet three state elementary education teachers' perceptions. These teachers work in a country side city in the state of Sao Paulo, each one works in a different grade – first grade, second grade and third grade of elementary school. We characterized the course according to the written language offered by these three teachers in 2013 under the structural context. It also included the possible contributions for their professional development. We performed the current PNAIC legislation study along with thesis and dissertation electronic research including three PNAIC universities: UNICAMP (Universidade de Campinas), UNESP (Universidade Esadual Paulista), and UFSCar (Universidade Federal de Sao Carlos), all linked to previous public policies before PNAIC. We also interviewed teachers and their PNAIC tutors, and we analyzed the School Management Plan; we listed the materials offered to teachers (classroom books), and for their tasks with students (board games and children's books). We especially relied on works by the following professionals: Ana Carolina Marsiglia, Bernadete Gatti, Claudio Félix dos Santos, Dermeval Saviani, Elaine Eliane P. de Souza, Lígia Marcia Martins, Magda Soares, Maria do Rosário Longo Mortatti, Maria Iolanda Monteiro, Newton Duarte, Romy Salomão e Sirley Tedesco. The results are based on teachers' understanding about the need of a public policy for teacher's training and fringe benefits such as scholarships and materials distribution not only for teachers' training but also children's books and literacy games. Nevertheless, there are intriguing facts that deserve special attention to be reviewed upon the agreement implementation: the steps that the proposals go through before reaching the students, such steps embodied by the universities coordination that train the teachers, study tutors, faculty formation and the professors, just to mention a few. It is clear that the several instances that the teacher's education has passed and all the interests involved are prone to distort the faculty proposal thus endowing the existing gaps in the formation books by leaving the original proposal behind. The strength of the teacher's formation offered by the PNAIC proposal became unfruitful to grant teachers' professional development since it has not even close to ease the harsh work conditions and the reality of the school community.